Peningkatan Keterampilan Profesional Guru-Guru SD Gugus Ganesha Windusari Magelang Melalui Pelatihan Implementasi Model Inquiry Based Learning (IBL) Bermuatan Six Pillars Of Character - Hartati Hartati; Novi Setyasto; Putri Yanuarita Sutikno; Renggani Renggani (Universitas Negeri Semarang, 2019)
Enactment of Permendikbud No. 22 of 2016 concerning Process Standards implies a shift in the teaching paradigm to a learning paradigm, the use of a scientific approach (scientific), and an integrated thematic so that it is necessary to apply problem-based learning. However, the reality on the ground is different. Based on the results of a preliminary study conducted in the Ganesha Windusari Cluster, Magelang consisting of 50 elementary school teachers and located on the slopes of Mount Sumbing, it shows that approximately 80% of teachers (or about 40 teachers) still have difficulty implementing disclosure-based learning/research in the classroom, especially in the manufacture of learning tools that contain the cultivation of attitudes or character values ​​in accordance with process standards. The solution that can be applied is the provision of training activities for the Implementation of the Inquiry Based Learning (IBL) Learning Model with Six Pillars of Character. The purpose of this service activity is to provide training to elementary school teachers in the Ganesha Group in implementing the IBL model containing the six pillars of character in learning in elementary school. The method of this service activity is in the form of training for elementary school teachers in the Dewadaru II Cluster. The training methods used in this service are: lecture, question and answer, practice, and simulation. This training activity was attended by 38 teachers of SD Gugus Ganesha with the training location at SDN Banjarsari, Windusari District, Magelang. The outputs resulting from this training activity are an increase in the knowledge and skills of teachers as indicated by: 1) the composition of 30 learning tools with the IBL model containing the six pillars of character; 2) an increase in the average post-test result (75.4) compared to the average pre-test result (32.6); 3) 25 out of 38 participants gave a very positive response to the quality of the training materials and 13 participants gave a positive response with an average score of 4.66.